A scoping review of systematic reviews on reducing lifestyle risk behaviours in disadvantaged groups. (20th October 2021) - South, E; Rodgers, M; Wright, K; Whitehead, M; Sowden, A
Abstract: Background: Lifestyle risk behaviours are key risk factors for non-communicable diseases. Some disadvantaged groups face particularly poor health outcomes, which may be exacerbated by high prevalence of risk behaviours. The aim of this scoping review was to identify and bring together evidence from systematic reviews on reducing risk behaviours in these groups and highlight where there is insufficient evidence to inform policy. Methods: MEDLINE and Embase were searched up to October 2020 for English language reviews, with supplementary searching in Epistemonikos and Health Systems Evidence. Systematic reviews reporting behavioural outcomes of interventions targeting smoking, alcohol use, diet or physical inactivity in nine disadvantaged groups were eligible. Reviews of population-level policies reporting differential effects for these groups and qualitative reviews of barriers or facilitators to change were included. Literature was mapped based on the group and behaviour targeted. Results: Ninety-two systematic reviews were included. The majority (n = 68) focused on low income or socio-economic status. Fewer reviews were identified that included prisoners (n = 14), deprived areas (n = 12), homeless people (n = 10), people with learning disabilities (n = 9), unemployed people (n = 3) and refugees or asylum seekers (n = 2). We identified no reviews on care leavers or Gypsies, Travellers or Roma. In total only 11 reviews targeted alcohol use. There were some gaps for specific group and behaviour combinations and no intervention reviews on refugees. Conclusions: A number of gaps were identified, highlighting where new syntheses or primary studies could add value. For example, reviews on interventions in refugees, Gypsies, Travellers and Roma, and care leavers could be useful for policy-making. Other useful contributions might include an overview of the perceptions of disadvantaged groups allowing common barriers to behaviour change to be identified as well as factors unique to specific groups. Key messages: Nearly 100 systematic reviews focused on reducing risk behaviours in disadvantaged groups; they addressed different combinations of behaviours and groups. Gaps in the literature were identified where new syntheses could make a useful contribution to developing programmes and policies.